2015
DOI: 10.1134/s1064226915080197
|View full text |Cite
|
Sign up to set email alerts
|

MIMO precoding for cooperative relay transmission

Abstract: In this paper, we design the scheme of information exchange for the multi directional two way relaying channels where each user pair would like to exchange message with its partner. The new scheme use transmission precoding vector to align the message from the same user pair. The signals from the same user pair are grouped together for network coding and cross pair interference can be canceled. We derive the explicit theoretical analysis for diversity gain. The simulation results are also provided to illustrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Zhong et al prepared aspirin‐loaded PLA/PEG blend composites by solution casting method and stated that they showed very good results in drug release 32 . Additionally, Wang et al doped MWCNT into the PLA/PEG blend solution and concluded that it improved its mechanical properties 33 …”
Section: Introductionmentioning
confidence: 99%
“…Zhong et al prepared aspirin‐loaded PLA/PEG blend composites by solution casting method and stated that they showed very good results in drug release 32 . Additionally, Wang et al doped MWCNT into the PLA/PEG blend solution and concluded that it improved its mechanical properties 33 …”
Section: Introductionmentioning
confidence: 99%